The Relationship of Mothers' Level of Knowledge on Menopause Concerning Personal Readiness for Monepause at Binjai Estate Health Center - Mardiani Purba (International Journal of Health and Social Behavior, 2024)
This study explores the relationship between mothers' knowledge of menopause and their personal readiness for this life stage at the Binjai Estate Health Center. Menopause, marked by the cessation of menstrual cycles, brings various physical and psychological changes. Adequate knowledge of menopause is essential for women to prepare both emotionally and physically for these changes. Using a quantitative cross-sectional design, the study involved mothers aged 45-55 years who attended the health center. Data were collected through structured questionnaires that evaluated the participants' understanding of menopause, including its symptoms, stages, and health implications, alongside their readiness to face these changes. The results indicated a significant correlation between knowledge and readiness for menopause. Mothers with higher knowledge levels were more prepared, taking proactive steps to manage symptoms and seek healthcare. In contrast, those with less knowledge experienced greater anxiety and uncertainty about the menopausal transition. The study highlights the crucial role of educational programs in equipping women with the knowledge needed to navigate menopause effectively. Health centers, such as the Binjai Estate Health Center, are vital in providing this education and support, thereby enhancing women’s readiness for menopause and improving their overall well-being.